School Desegregation, School Choice, and Changes in Residential Location Patterns by Race - Baum-Snow, Nathaniel; Lutz, Byron F (American Economic Review, 2011)
This paper examines the residential location and school choice responses to the desegregation of large urban public school districts. We decompose the well documented decline in white public enrollment following desegregation into migration to suburban districts and increased private school enrollment, and find that migration was the more prevalent response. Desegregation caused black public enrollment to increase significantly outside of the South, mostly by slowing decentralization of black households to the suburbs, and large black private school enrollment declines in southern districts. Central district school desegregation generated only a small portion of overall urban population decentralization between 1960 and 1990.